Суб'юнктори в детермінативному реченні німецького медичного дискурсу - Олексієнко, Алла Валеріївна; Oleksiienko, Alla (Дрогобицький держвний педагогічний університет імені Івана Франка, 2019)
Стаття присвячена аналізу зв’язкових засобів у детермінативному реченні німецького медичного недискретного дискурсу. Метою дослідження є формально-граматична класифікація суб’юнкторів у детермінативному підрядному реченні та аналіз їх вживання в різних логіко-семантичних типах речень. Розвідка текстів медичного дискурсу дала змогу зробити висновок, що суб’юнктори в детермінативному підрядному реченні поділяються на чотири структурно-семантичні типи (прямого і непрямого об’єкта, супровідні та каузальні). Також проведено класифікаційний аналіз вживання релятивів у коментувальних, комітативних та каузальних логіко-семантичних типах підрядних речень. The study of different types of discourses depending on the nature of communication subjects is of particular importance in the development of modern linguistics. Medical non-discrete discourse is the communication between specialists equal in their status who build communication rich on specific terminology and complex syntactic structures. Among them are determinative subordinate sentences that are aimed at providing optional information extend the main sentence as a whole and always being introduced by subjunctors. The article is devoted to the analysis of conjunctive means of determinative clause in the medical non-discrete discourse of the German language, their formal-grammatical classification and the logical-semantic aspect. One of the defining features of determinative subordinate sentences is syndetic coordination, which means that conjunctions (subjunctors) are always present for marking the relations between the main and the subordinate sentences. However, here there is also a specificity of this type of sentence in German language, namely these clauses are introduced not by conjunctions, but by connecting words belonging to the category of relative pronouns, or more precisely – to pronoun adverbs with w-root. As the analysis shows pronoun adverbs in a determinative clause are divided into four structural-semantic types: pronoun adverbs of direct and indirect object, the accompanying and causal pronoun adverbs. The most numerous, but not more commonly used is a group of subjunctors of an indirect object. The logic-semantic structure is represented by three types of determinant sentences – commented, comitative, causal. In the first group predominates the use of subjunctors of the direct object, comitative determination is explicitly related to the pronoun adverb “wobei”, and causal clauses are characterized by the use of subjunctors “weswegen, weshalb, woraufhin” and relative pronouns in specific causal context.
Subjunctors in determinative sentence of German medical discourse
orcid.org/0000-0002-5095-6065
Keywords: медичний дискурс; суб’юнктор; релятив; детермінативне підрядне речення; medical discourse; subjunctor; relative pronoun; pronoun adverb; determinative clause